Genetic variants associated with inherited cardiovascular disorders among 13,131 asymptomatic older adults of European descent - Paul Lacaze (Nature Portfolio, 2021)
Abstract Genetic testing is used to optimise the management of inherited cardiovascular disorders that can cause sudden cardiac death. Yet more genotype–phenotype correlation studies from populations not ascertained on clinical symptoms or family history of disease are required to improve understanding of gene penetrance. We performed targeted sequencing of 25 genes used routinely in clinical genetic testing for inherited cardiovascular disorders in a population of 13,131 asymptomatic older individuals (mean age 75 years) enrolled in the ASPREE trial. Participants had no prior history of cardiovascular disease events, dementia or physical disability at enrolment. Variants were classified following ACMG/AMP standards. Sudden and rapid cardiac deaths were clinically adjudicated as ASPREE trial endpoints, and assessed during mean 4.7 years of follow-up. In total, 119 participants had pathogenic/deleterious variants in one of the 25 genes analysed (carrier rate of 1 in 110 or 0.9%). Participants carried variants associated with hypertrophic cardiomyopathy (N = 24), dilated cardiomyopathy (N = 29), arrhythmogenic right-ventricular cardiomyopathy (N = 22), catecholaminergic polymorphic ventricular tachycardia (N = 4), aortopathies (N = 1), and long-QT syndrome (N = 39). Among 119 carriers, two died from presumed sudden/rapid cardiac deaths during follow-up (1.7%); both with pathogenic variants in long-QT syndrome genes (KCNQ1, SCN5A). Among non-carriers, the rate of sudden/rapid cardiac deaths was significantly lower (0.08%, 11/12936, p < 0.001). Variants associated with inherited cardiovascular disorders are found in asymptomatic individuals aged 70 years and older without a history of cardiovascular disease.